PEDOMAN TATA CARA WUDHU DAN TAYAMUM DENGAN BAIK DAN BENAR MENURUT SUNNAH DI PEMBELAJARAN KEMUHAMMADIYAHAN BERBASIS ANDROID IKEST MUHAMMADIYAH PALEMBANG - Ridwan Hakim; Arif Fadillah (IKesT Muhammadiyah Palembang, 2023)
ABSTRACT Background: learning the procedures for ablution and tayammum is fundamental in islam, and correct knowledge of these procedures is a must. therefore, the development of this application will enable users, especially for them to learn in an interactive and effective way. apart from that, the use of mobile technology in religious learning can also enable a wider dissemination of religious knowledge, allowing more individuals to understand and follow the procedures for ablution and tayamum correctly. Research Method: this research uses data collection techniques using qualitative methods. namely by interviews and observations as well as a waterfall design. Results: the results of the research were to create